A hard X-ray view of luminous and ultra-luminous infrared galaxies in GOALS – I. AGN obscuration along the merger sequence. Issue 4 (19th July 2021) - Ricci, C; Privon, G C; Pfeifle, R W; Armus, L; Iwasawa, K; Torres-Albà, N; Satyapal, S; Bauer, F E; Treister, E; Ho, L C; Aalto, S; Arévalo, P; et al.
ABSTRACT: The merger of two or more galaxies can enhance the inflow of material from galactic scales into the close environments of active galactic nuclei (AGNs), obscuring and feeding the supermassive black hole (SMBH). Both recent simulations and observations of AGN in mergers have confirmed that mergers are related to strong nuclear obscuration. However, it is still unclear how AGN obscuration evolves in the last phases of the merger process. We study a sample of 60 luminous and ultra-luminous IR galaxies (U/LIRGs) from the GOALS sample observed by NuSTAR . We find that the fraction of AGNs that are Compton thick (CT; $N_{\rm H}\ge 10^{24}\rm \, cm^{-2}$ ) peaks at $74_{-19}^{+14}{{\ \rm per\ cent}}$ at a late merger stage, prior to coalescence, when the nuclei have projected separations ( d sep ) of 0.4–6 kpc. A similar peak is also observed in the median N H [$(1.6\pm 0.5)\times 10^{24}\rm \, cm^{-2}$ ]. The vast majority ($85^{+7}_{-9}{{\ \rm per\ cent}}$ ) of the AGNs in the final merger stages ( d sep ≲ 10 kpc) are heavily obscured ($N_{\rm H}\ge 10^{23}\rm \, cm^{-2}$ ), and the median N H of the accreting SMBHs in our sample is systematically higher than that of local hard X-ray-selected AGN, regardless of the merger stage. This implies that these objects have very obscured nuclear environments, with the $N_{\rm H}\ge 10^{23}\rm \, cm^{-2}$ gas almost completely covering the AGN in late mergers. CT AGNs tend to have systematically higher absorption-corrected X-ray luminosities than less obscured sources. This could either be due to an evolutionary effect, with more obscured sources accreting more rapidly because they have more gas available in their surroundings, or to a selection bias. The latter scenario would imply that we are still missing a large fraction of heavily obscured, lower luminosity ($L_{2-10}\lesssim 10^{43}\rm \, erg\, s^{-1}$ ) AGNs in U/LIRGs.